Multidrug-Resistant Escherichia coli in Costa Rican Domestic Wastewater Treatment Plants Maintains Horizontal Transfer Capacity of Resistance Determinants in Effluents - Rivera Montero, Luis César (2023)
This study was conducted to evidence the dissemination potential of antibiotic resistance genetic elements in E. coli isolates of Costa Rican domestic wastewater treatment plants (WWTPs). Few studies have addressed this phenomenon in WWTPs in Central America. Phenotypical resistance profiles to β-lactams, quinolones, aminoglycosides, phenicols, tetracyclines, and folate pathway inhibitors of 133 Escherichia coli isolates from the influent and effluent of two urban WWTPs located in the Greater Metropolitan Area of Costa Rica were described. Thirty multidrug-resistant profiles were identified and grouped into 15 genetic clones by ERIC-PCR; 6 of 15 genetic clones were from effluents. Six of the seven examined genes (sulI, sulII, intI1, intI2, blaTEM, and tetA) were found in multidrug-resistant isolates, whereas blaOXA was absent. The horizontal gene conjugation test confirmed the gene transfer capacity of all tested isolates n = 8. Multidrug-resistant isolates in effluents with horizontal gene transfer capacity suggest that Costa Rican WWTPs represent spots related to antibiotic resistance spread to the environment. In domestic WWTPs, we found that nearly 22% of E. coli isolates presented a multidrug-resistant phenotype capable of transferring their resistance determinants by conjugation processes.